Assessing the status of social capital and its relationship with organizational voice and silence in kermanshah university of medical science - Heydari Soreshjani, Nasrin; Safari, Yahya; Rezaei, Bijan (International Journal of Engineering and Technology, 2018)
The present study aimed to assessing the status of social capital and its relationship with organizational Voice and Silence in Kermanshah University of Medical Science in 2017-18. This research was an applied one in terms of the purpose and used a descriptive correlational design for data collection. The population included all employees working at Kermanshah University of Medical Sciences (n = 350) and a sample of 186 subjects were selected using random stratified sampling method. Data were collected using three standard question-naires including Social Capital by Nahapiet and Ghoshal (1997), Organizational Voice by Hames, (2012) and Organizational Silence by Vakola (2005). Cronbach’s alpha coefficient was calculated for measuring the reliability of the questionnaire: social capital questionnaire (0.96), organizational silence and organizational voice questionnaire(0.85), (0.95). In addition, the content validity of the questionnaire was confirmed by professors and experts. Data were analyzed using Pearson correlation coefficient via SPSS v. 21 software. According to the results, there is a negative and significant correlation between social capital and organizational silence (P = 0.01, r = -0605) and a positive and significant correlation between social capital and organizational voice (P = 0/001, r = 0.675) among the employees working at Kerman-shah University of Medical Sciences.